Differential Behavioral and Neurobiological Effects of Chronic Corticosterone Treatment in Adolescent and Adult Rats - Li, Jitao; Xie, Xiaomeng; Li, Youhong; Liu, Xiao; Liao, Xuemei; Su, Yun-Ai; Si, Tianmei (Frontiers in Molecular Neuroscience, 2017)
Adolescence is a critical period with ongoing maturational processes in stress-sensitive systems. While adolescent individuals show heightened stress-induced hormonal responses compared to adults, it is unclear whether and how the behavioral and neurobiological consequences of chronic stress would differ between the two age groups. Here we address this issue by examining the effects of chronic exposure to the stress hormone, corticosterone (CORT), in both adolescent and adult animals. Male Sprague-Dawley (SD) rats were injected intraperitoneally with CORT (40 mg/kg) or vehicle for 21 days during adolescence (post-natal day (PND) 29–49) or adulthood (PND 71–91) and then subjected to behavioral testing or sacrifice for western blot analyses. Despite of similar physical and neuroendocrine effects in both age groups, chronic CORT treatment produced a series of behavioral and neurobiological effects with striking age differences. While CORT-treated adult animals exhibited decreased sucrose preference, increased anxiety levels and cognitive impairment, CORT-treated adolescent animals demonstrated increased sucrose preference, decreased anxiety levels, and increased sensorimotor gating functions. These differential behavioral alterations were accompanied by opposite changes in the two age groups in the expression levels of brain-derived neurotrophic factor (BDNF), the phosphorylation of the obligatory subunit of the NMDA receptor, GluN1, and PSD-95 in rat hippocampus. These results suggest that prolonged glucocorticoid exposure during adolescence produces different behavioral and neurobiological effects from those in adulthood, which may be due to the complex interaction between glucocorticoids and the ongoing neurodevelopmental processes during this period.